2013
DOI: 10.4081/aiua.2013.2.86
|View full text |Cite
|
Sign up to set email alerts
|

Comparative randomized study on the efficaciousness of endoscopic bipolar prostate resection versus monopolar resection technique. 3 year follow-up

Abstract: Objective: Transurethral resection of the prostate (TURP) is the current optimal therapy for the relief of bladder outflow obstruction, with subjective and objective success rate of 85 to 90%. Aim of this study was to evaluate efficacy and safety of Plasmakinetic energy (Gyrus electro surgical system), which produces vaporization of tissue immersed in isotonic saline against standard monopolar transurethral resection of the prostate. Results: Comparative data on IPSS symptom score, IIEF-5, Qol, PSA, peak urina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 13 publications
2
27
1
2
Order By: Relevance
“…8 In recent years (2009-2013), a number of new RCTs, including multicenter and international studies, have been published. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, it is necessary to conduct a new systematic review and metaanalysis of RCTs that assesses the efficacy and safety (primary outcomes) of M-TURP and B-TURP in patients with BPO.…”
mentioning
confidence: 99%
“…8 In recent years (2009-2013), a number of new RCTs, including multicenter and international studies, have been published. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Therefore, it is necessary to conduct a new systematic review and metaanalysis of RCTs that assesses the efficacy and safety (primary outcomes) of M-TURP and B-TURP in patients with BPO.…”
mentioning
confidence: 99%
“…In TURP, by bipolar technology, the surgeon has a clearer field (4). There are many studies that reported greater amount of blood loss during monopolar TURP in contrast with bipolar TURP (10).…”
Section: Discussionmentioning
confidence: 99%
“…However, several maleffects such as warming of deeper tissue and provocation of nerves and muscles may happen (3). In bipolar system, for the reason of putting the positive and negative electrode on the same axis of resectoscope and applying high local electrical current, accompanied with less negative effects at distance axis (4).…”
Section: Introductionmentioning
confidence: 99%
“…La Asociación Europea de Urología la recomienda cuando la próstata tiene entre 30 y 80 mL (12,20). Los resultados de las técnicas monopolar y bipolar para llevarla a cabo son muy similares, pero, al parecer, la bipolar tiene un perfil de seguridad más favorable, ausencia del síndrome de pos-RTUP, menos sangrado intraquirúrgico y posoperatorio y menor tasa de retención aguda de orina (RAO) por coágulos (17,(19)(20)(21)(22).…”
Section: Resección Transuretral De Próstata (Rtup)unclassified